2018
DOI: 10.1080/13625187.2018.1539161
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and evaluation of quality of life and well-being in individuals having or having had fertility problems: a systematic review

Abstract: Objectives: The aims of this study were: (1) to identify which measurement instruments are used in practice to assess the quality of life or well-being of individuals with and without (sub)fertility; (2) to describe the design and outcomes of studies comparing quality of life or well-being of individuals with and without fertility problems; and (3) to determine which of the outcomes of the identified studies could be used in cost-utility studies. Methods: A systematic literature review was performed of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Translating quality of life measures collected in primary research into utility values required for generating QALYs to apply in CEAs implies the use of preference-based instruments [16]. It is common for studies assessing infertility or sub-fertility-related quality of life to use such instruments; nonetheless it is not common for these studies to report utilities or HRQoL measures that can be converted to utilities [21].…”
Section: Valuing Outcomes In Marmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating quality of life measures collected in primary research into utility values required for generating QALYs to apply in CEAs implies the use of preference-based instruments [16]. It is common for studies assessing infertility or sub-fertility-related quality of life to use such instruments; nonetheless it is not common for these studies to report utilities or HRQoL measures that can be converted to utilities [21].…”
Section: Valuing Outcomes In Marmentioning
confidence: 99%
“…This approach fails to take into consideration that the perception of infertility and involuntary childlessness changes over time as people adapts, and over time there can often be limited differences in HRQoL between those with children and involuntarily childless couples [41e43]. Due to the limitations of many patient-reported outcome instruments, past reviews suggest that available HRQoL studies in infertile couples are not suitable for capturing utilities for use in CEAs [21]. When these observations are coupled with the varying biological effects of being pregnant, and the changing perception of involuntary childlessness over time, there are likely to be limits to applying QALY-based economic evaluations in MAR couples.…”
Section: Assessing the Costs And Effects Of Marmentioning
confidence: 99%
“…The conventional method of its diagnosis involves examining semen parameters ( WHO, 2023 ), where sperm count has decreased by over 50% in the last 40 years, with a continuous decline of 2.6% per year among Western men ( Barratt et al, 2017 ; Levine et al, 2023 ). This decline not only impacts fertilization rates but also leads to increased disease burden and healthcare costs ( Hubens et al, 2018 ; Kasman et al, 2020 ; Levine et al, 2017 ). The root causes of male infertility are complex and diverse, including (epi)genetics, psychology, lifestyle, pathogens, and environmental insults (such as xenobiotics, oxidative stress, heat stress and chemotherapeutic agents) – all of which require further research to better understand their contributions ( Aitken, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical studies have shown that some items in the FertiQoL are poorly understood in a Chinese cultural setting and irrelevant to the Chinese health service system [ 21 ]. Generic HRQoL instruments such as EuroQol-5 dimensions-5 levels (EQ-5D-5L), Medical Outcomes Study 36-Item Health Survey (SF-36), WHO Quality of Life Measure (WHOQOL-BREF) have been frequently used to assess HRQoL among infertility patients [ 9 , 22 , 23 ]. However, the generic measures are not able to include important disease-specific domains, which are useful to detect clinical changes specific to infertility.…”
Section: Introductionmentioning
confidence: 99%